Nothing is impossible reflections on a new life - Reeve, Christopher 1952-2004 (Random House, 2002)
Drawing on his own personal experiences and those of others, the author explains how to overcome seemingly insurmountable problems and challenges and advocates living life fully with gratitude, zeal, and curiosity.
Keywords: Reeve, Christopher <1952-2004>; Reeve, Christopher -- 1952-2004; Acteurs - États-Unis - Biographies; Tétraplégiques - États-Unis - Biographies; Actors -- United States -- Biography; Quadriplegics -- United States -- Biography; Autobiografie; USA; Biografie